That awful secret of the wood' : the forest and the EcoGothic - Parker, Elizabeth (Trinity College (Dublin, Ireland). School of English, 2016)
When we imagine the forest, we tend towards extremes. It is commonly read as a binary space: as either ‘good’ or ‘bad’. When it is ‘good’, it is a remedial setting of wonder and enchantment; when it is ‘bad’, it is a dangerous and terrifying wilderness. It is with its fearsome associations that this thesis is concerned. Sarah Maitland, in her book Gossip From the Forest (2012), argues that ‘inside most of post-enlightenment and would-be rational adults, there is a child who is terrified by the wild wood’.1 The implication in her wording is that the modern adult who fears the forest does so despite the fact that he or she is ‘post-enlightenment’ and ‘would-be rational’. It is suggested, therefore, that such fears are today not only unfounded, but regressive and irrational. Nonetheless, as she continues, there is much evidence to suggest that we continue to be ‘terrified by the wild wood’. Popular culture abounds with seemingly infinite examples of the foreboding forest. It is, as a site of trial, trepidation, and terror, one of the most enduring and pervasive in our fictions. The central question of this thesis, therefore, is why do we continue to find this landscape so frightening? This thesis seeks to answer this question by examining a range of twentieth and twenty-first century Gothic texts, each of which features a fearsome forest.
Embargo End Date: 2022-01-01
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin, 2016